Evaluation of Negative Cognitions in Children and Adolescents: Children’s Automatic Thoughts Scale - Derya Atalan ERGÝN; Emine Gül KAPÇI (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Objective: Objective: The aim of the present study is to evaluate psychometric properties of the Children’s Automatic Thoughts Scale to children and adolescents. Method: A total of 534 children and adolescents aged 9-16 participated in the study. They attended elementary schools in Ankara. Of these participants 276 were girls and 258 were boys. The mean age of the group was 12.30 (SD=1.26).They were attending 4th to 8th grade of the elementary schools. Results: Exploratory and Confirmatory factor analyses confirmed the four factor model (Schniering and Rapee 2002). The four factor model explained 50% of variance. The first factor was social threat and 31.72% of the total variance. Followed by personal failure, hostility and physical treat factors explaining 8.32%, 5.80% and 5.10 % of the total variance. Social threat was found to be explaining the higher variance in the present study while personal failure was the first factor explaining higher variance in the original study. Test-rest reliabilities with two weeks interval demonstrated that the Children’s Automatic Thoughts Scale is a reliable instrument(r=.90). Cronbach Alpha was found to be and .94. These reliability and validity analyses supported that Children’s Automatic Thoughts Scale could be used with Turkish children. Conclusion: Children’s Automatic Thoughts Scale, evaluates the presence and severity of negative cognition in children and adolescents, could be utilized in research and clinical practice. It could also be used in educational settings where the thought content of children and adolescents are important in areas such as friendship, academic success and bullying. (Journal of Cognitive Behavioral Psychotherapy and Research 2013, 2: 72-77) [JCBPR 2013; 2(2.000): 72-77]